Examining the shifting patterns of poaching from a long-term law enforcement intervention in Sumatra. (December 2016) - Risdianto, Dian; Martyr, Deborah J.; Nugraha, Rudijanta T.; Harihar, Abishek; Wibisono, Hariyo T.; Haidir, Iding A.; Macdonald, David W.; D'Cruze, Neil; Linkie, Matthew
Abstract: Current levels of illegal wildlife trade for many in-demand species are unsustainable and place them at a heightened risk of extinction. While several Asian protected areas standout for their remarkable successes in tackling poaching, the threat continues nonetheless. We analyse a decade of law enforcement data from a Sumatran protected area to investigate tiger and prey poaching trends, the arrests and subsequent prosecution of those involved. Some 3882 snare traps were destroyed, but a recent spike in tiger poaching revealed that twice the number of snares were annually encountered in 2013 and 2014 than the eight preceding years. We detected a change in the techniques employed for poaching tigers from 2011 onwards, with more frequent encounters of snare trap clusters that contained six or more tiger traps set in a single location. Comparing monthly patterns of poaching within years revealed an increase in deer, but not tiger, poaching during the month of Ramadan. This result confirmed long-held views by the ranger teams that local demand for meat increases in the build up to Idul Fitri, a main Islamic holiday. Finally, from 24 law enforcement operations conducted, 40 tiger poachers/traders were arrested with > 90% being prosecuted. However, the fines and prison sentences issued were much lower than the maximum available, and the highest sentence was for firearms possession and not illegal activities towards wildlife. Our site-based study demonstrates what can be achieved, but also identifies areas for strengthening the sub-national and national law enforcement response to an escalating tiger poaching trend.